The usefulness of a taphonomic approach for studies of Pleistocene mammals - Pawłowska, Kamilla (Geologos, 2010)
The potential usefulness of taphonomical research for studies of Pleistocene mammal remains is detailed. The required taphonomical research involves two stages. The ﬁrst one is the biostratinomical stage, which concerns the time between the death of the organism and its burial; for this time-span, the spatial distribution of the remnants is analysed, as well as the weathering marks, the activity of predators (i.e. gnawing and digestion), the inﬂuence of temperature, intentio-nal human activity, rodent marks (i.e. gnawing), and trampling. in the second one is the diagenetic stage, which deals with the time-span from the burial of the remnants to their discovery; for this time-span, the inﬂuence of physical and chemical processes (including diagenetic alterations of the deposit, the inﬂuence of water, and plant-root marks) are considered. The application of taphonomical analysis provides the possibility of reconstructing the environmental conditions under which the skeleton or bone complex was preserved, as well as the depositional history of the bones (postconsumption remnants, ﬂood remains, accumulation of bones by predators). This opens new possibilities for the study of Pleistocene bones in Poland.